SAHKAH HUKUM YANG BURUK SECARA MORAL ? PERDEBATAN ANTARA LON LUVOIS FULLER DAN H.L.A. HART - Petrus Bello (Fakultas Hukum Universitas Kristen Indonesia, 2023)
The concept of natural law, which was inherited by Thomas Aquinas, is still attractive. In the 20th century, his thoughts were re-examined and used as a basis by several legal philosophers, one of whom was Lon Luvois Fuller. Fuller is considered successful in actualizing Aquinas' thoughts in the realm of 20th century thought. Natural law is understood as a theory which states that law and morality have an absolute relationship (necessary relation); that the validity of law (rules, precedent, judge's decision) depends on its conformity with morality. The absolute link between law and morality according to Fuller is evident in the procedures that apply in the contemporary legal system which according to him reflects moral principles or legal morality. Fuller's thoughts were met with strong resistance from H.L.A. Hart stated that the moral principles according to Fuller are legal morality not as moral principles, but as legal principles.